2008
DOI: 10.1167/iovs.07-0280
|View full text |Cite
|
Sign up to set email alerts
|

Reproducibility and Clinical Relevance of the Ocular Response Analyzer in Nonoperated Eyes: Corneal Biomechanical and Tonometric Implications

Abstract: The ORA provides reproducible corneal biomechanical and IOP measurements in nonoperated eyes. Considering the effect of ORA, corneal biomechanical metrics produces an outcome-significant IOP adjustment in at least one quarter of glaucomatous and normal eyes undergoing noncontact tonometry. Corneal viscoelasticity (CH) and resistance (CRF) appear to decrease minimally with increasing age in healthy adults.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

14
84
2
3

Year Published

2009
2009
2016
2016

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(103 citation statements)
references
References 54 publications
14
84
2
3
Order By: Relevance
“…Consecutive corneal measurements can be taken with ORA. 14 We can estimate that IOP by ORA is less influenced by corneal properties. 10 In this way, we can say that ORA is a device that measures corneal properties and IOP together.…”
Section: Discussionmentioning
confidence: 93%
“…Consecutive corneal measurements can be taken with ORA. 14 We can estimate that IOP by ORA is less influenced by corneal properties. 10 In this way, we can say that ORA is a device that measures corneal properties and IOP together.…”
Section: Discussionmentioning
confidence: 93%
“…84 These parameters, CH and CRF, have been shown to be reproducible in nonoperated healthy eyes. 85 Some authors have demonstrated that CH and CRF are significantly lower in keratoconic eyes than in normal eyes. 82,83 Ortiz et al 83 compared the ORA outcomes in 165 normal eyes and 21 eyes with keratoconus (47% grade I according to the Amsler-Krumeich grading system), obtaining the mean values of 10.8 G 1.5 mm Hg and 7.7 G 1.3 mm Hg, respectively.…”
Section: Corneal Biomechanics In Keratoconusmentioning
confidence: 99%
“…[8][9][10][11] The non-contact ocular response analyser (ORA: Reichert Ophthalmic Instruments, Buffalo, NY, USA) provides a corneal compensated IOP measurement (IOPcc) that avoids several of the imitations of GAT. 7,8,10,[12][13][14][15] The ORA has received attention in the areas of glaucoma, corneal disorders, and refractive surgery. It also provides a Goldmann correlated IOP (IOPg) value and a waveform score (WS) designed to guide the clinician in selecting high quality measurements.…”
Section: Introductionmentioning
confidence: 99%